Dynamic behaviour in mode I fracture toughness of CFRP as a function of temperature. (October 2019) - Machado, J.J.M.; Hayashi, A.; Sekigushi, Y.; Campilho, R.D.S.G.; Marques, E.A.S.; Sato, C.; da Silva, Lucas F.M.
Highlights: Influence of high strain rate and testing temperature on GIC of CFRP. DCB specimens were tested to determine GIC as a function of temperature under impact. LIM technique was used to measure the crack length. With the increase of the testing temperature, an increase of about 50% of GIC was registered. The test velocity was found not to be constant. Abstract: The aim of this work is to assess the influence of high strain rates and testing temperature on the fracture energy in mode I, GIC, of carbon fibre reinforced plastic (CFRP) plates. Double cantilever beam (DCB) specimens were tested to determine GIC as a function of temperature (24 and 80 °C) under an impact load of 4.7 m/s (using a falling-wedge impact test machine), with the results being compared with the values previously determined by the authors under quasi-static loads. This work has demonstrated a significant influence of the testing temperature on the GIC of composite materials, as this value greatly increased for higher temperatures. On the other hand, a less significant influence of the strain rate on GIC was found, which slightly decreased by increasing the strain rate.